NiFeMo layered triple hydroxide and MXene heterostructure for boosted oxygen evolution reaction in anion exchange membrane water electrolysis - Pal, Santanu; Chaturvedi, Ekta; Das, Chandni; Sinha, Nibedita; Ahmed, Tanbir; Roy, Poulomi (Nanoscale, 2025)
Efficient, low cost and stable electrocatalysts are highly desirable for overcoming the sluggish kinetics of the oxygen evolution reaction (OER) in alkaline water electrolysis for hydrogen production. Interfacial engineering of heterostructures is quite beneficial for improving charge transfer efficiency at the interface. In this context, heterostructures of layered triple hydroxides (LTHs) and MXenes have shown great potential as OER electrocatalysts owing to their 2D-2D structure and unique physiochemical properties. Coupling LTHs with MXenes can potentially enhance their conductivity and stability, thereby boosting OER activity. In this study, we report a heterointerface between NiFeMo-LTH on Ti3C2Tx MXene, which exhibited superior catalytic activity and stability in alkaline freshwater and seawater, reducing the activation energy. Importantly, the heterostructure achieved a current density of 100 mA cm-2 at the cost of 292 mV and 340 mV overpotentials in alkaline saline water and real seawater, respectively, and showed robustness over 100 h without hypochlorite formation in alkaline real seawater, exhibiting corrosion-resistant behaviour. Moreover, NiFeMo-LTH/MXene explored in alkaline anion exchange membrane water electrolyzer (AEMWE) achieved a current density of 750 mA cm-2 at 2.16 V cell voltage at an operating temperature of 60 degrees C with an energy efficiency of 60.5%. Raman analysis and XPS analysis post stability test demonstrated easy electron transfer from LTH to MXene at the heterointerface, leading to the formation of NiOOH electroactive species that facilitated the OER activity.